Heterotopic Ossification in Total Ankle Arthroplasty: Case Series of Novel Implant and Systematic Review. Issue 3 (14th September 2018) - Bemenderfer, Thomas; Anderson, Robert; Escudero, Mario; Waly, Feras; Wing, Kevin; Davis, W. Hodges
Category: Ankle Arthritis Introduction/Purpose: Heterotopic ossification (HO) following total ankle arthroplasty (TAA) is a known sequela and has been reported to contribute to reduced postoperative range of motion and poor patient functional outcomes. However, conflicting results have been reported in the literature with respect to the correlation between HO and clinical outcome. As new strategies and implants continue to be designed, it is important to understand what instruments for measuring the outcome of treatment are important to assess when evaluating outcome measures in TAA. The present study documents the incidence of HO and functional outcome for the novel 2 component fixed bearing Infinity Total Ankle System prosthesis at minimum of two year follow up and reports a systematic review of the literature. Methods: We reviewed the incidence, degree of severity, and functional outcome in 67 consecutive patients who underwent primary Infinity TAA at two North American tertiary medical centers between 2013 and 2015 in a prospective observational study. Radiographic and functional outcome data was collected preoperatively, at 6 to 12 months postoperatively, and annually thereafter. In addition, we conducted a systematic review of studies reporting the incidence of HO following TAA. We included peer-reviewed studies reporting on at least 20 TAAs with minimum follow up of two years. Results: While the incidence of HO was 68% at 2.4 years in the 67 patients who underwent primary Infinity TAA, there was no association between HO and AOFAS (HO 73.9, no HO 55.0), SF36-PCS (HO 50.1, no HO 45.2), FFI (HO 22.1, no HO 26.4), and VAS (HO 2.6, no HO 2.3). Fourteen studies with 1201 TAAs were included. The overall incidence of HO following TAA was approximately 56.6% at average 3.8 years with a wide range (range, 22.2-100%). Four studies (299 ankles) did not address functional outcomes. Nine studies (822 ankles) reported no association between functional outcomes and HO. One study (80 ankles) reported a statistically significant difference in range of motion of 7 degrees of dorsiflexion and a 7-point difference in AOFAS score. Conclusion: There was no association between HO and functional outcome in our observational cohort. Only one study demonstrated statistically significant differences in range of motion and functional outcome due to HO. Although the minimal clinical important difference in ankle dorsiflexion and AOFAS has not been established in TAA, these differences are below the minimal clinical important difference established in other foot and ankle procedures. Available data, including the results in our 67 patients, suggests that clinical function is independent of the presence of HO.